Úspěšnost kadaverózních náhrad předního zkříženého vazu kolenního kloubu se zaměřením na subjektivní spokojenost pacientů - Sklenský, Jan; Vališ, Petr; Repko, Martin; Rouchal, Marek; Maršálek, Miloslav; Hrůzová, D (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2017)
PURPOSE OF THE STUDY A retrospective evaluation of the success rate of revision ACL reconstruction performed using BTB allograft in terms of the life expectancy of the procedure up to and over five years from surgery. MATERIAL AND METHODS Over a ten-year period, from 2003 to 2013, we performed 47 revision ACL reconstruction surgeries. The majority of the primary ACL reconstructions using BTB autografts were not performed at our site. The group observed included 16 women (34%) and 31 men (66%). The women were aged between 25 and 48 years, the median age being 32.5, and the men were aged between 25 and 46 years with the median age of 35. We were able to make a full pre- and post-operative evaluation of 22 out of 47 patients who underwent secondary ACL reconstruction surgery using a cadaverous BTB graft. This evaluation included an objective clinical testing and a subjective evaluation of the function and stability of the knee joint using the Tegner activity score, Lysholm score, and a modified Cincinatti score. The set of 22 patients was split into two groups: up to five years from revision surgery and over five years from the procedure. RESULTS In the group of patients who were fully evaluated within five years of revision reconstruction there was an average improvement of 16.4 points on the Cincinatti score, 19.9 points on the Lysholm score, and an upward movement averaging 1.5 levels on the Tegner activity score. In the over five years from surgery category the average improvement was 15.5, 15.9, and 1.2 levels upward movement, respectively. We were unable to prove a significantly increased level of failure in BTB allografts after five and more years from revision ACL reconstruction. DISCUSSION The two strongest factors affecting the life expectancy of ACL replacements are the age of the patient and the type of the graft used, allograft or autograft. The most at risk, in terms of how long the graft will last, is the age group of 10 - 19 years old. With each ten-year increase in age the risk of rupture is reduced more-or-less by half. Patients with ACL allograft replacement show a fourfold increased risk of the graft rupturing. The younger and more active the patient requiring revision ACL reconstruction is, the greater the need for an autograft. If an allograft has been used in revision reconstruction on an athlete, a great emphasis must be placed on the necessity of delaying the return to previous sporting activities for at least nine months. CONCLUSIONS The mid-term results of revision ACL reconstruction show that, subject to reasonable levels of stress, a correctly performed procedure using cadaverous BTB grafts is a good option to restore the stability of the knee joint over a period of five years and more from surgery. An increased incidence of reruptures or greater insufficiency of the cadaverous graft were not evident in our group after five and more years. The risk of cadaverous grafts failure is just like in the autologous replacement directly linked to the return to sport interval, frequency and intensity of stress to which the graft is subjected over a long period of time. The risk of rerupture is always higher in allograft reconstructions that have already stood in need of restructuring for a longer period of time. For this reason, a delay in returning to sports activity must be emphasized. As a rule, we recommend a return to full athletic training only after nine months to a year after surgery. Key words: anterior cruciate ligament, revision ACL reconstruction, tendon graft insufficiency, BTB autograft insufficiency, BTB allograft of the ACL, cadaverous BTB graft, ACL graft rerupture.
Keywords: výsledek terapie; spokojenost pacientů; Treatment Failure; štěp kost-čéškový vaz-kost; Male; neúspěšná terapie; Bone-Patellar Tendon-Bone Grafting; Adult; dospělí; mužské pohlaví; Patient Satisfaction; Treatment Outcome; lidé; ženské pohlaví; Humans; Reoperation; Female; lidé středního věku; reoperace; Middle Aged